Implementasi Metode Fuzzy Logic Dalam Perancangan Aplikasi Pemantauan Serta Kontrol Ph, Tds, Dan Suhu Pada Larutan Tanaman Hidroponik Pakcoy Menggunakan Arduino Berbasis Android - Reynaldo Reynaldo; Alvino Octaviano (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2022)
Hydroponics is a method of growing plants with water media without using soil media and prioritizing the fulfillment of plant nutritional needs. A hydroponic cultivation system that circulates air and nutrients using the Deep Flow Technique (DFT) method. Pakcoi vegetables developed on the Serpong Farm Hydroponic plantation. The activities carried out are measuring pH, TDS, and temperature levels in the media from hydroponic plants still using a simple meter which causes it to be ineffective, can cause reading errors in these levels, and It takes time to concentrate the nutrient solution. This study aims to build an Android-based system that can control nutrient levels and pH automatically using the Fuzzy Logic Sugeno method with stages starting from fuzzification, rule application, defuzzification and output as decision making from the system. The Fuzzy Logic model with the Takagi-Sugeno-Kang method is applied to the Arduino Mega 2560 using the C programming language.